Toll-Like Receptors and Human Disease: Lessons from Single Nucleotide Polymorphisms - Lin, Yi-Tzu; Verma, Amanda; P. Hodgkinson, Conrad (Current Genomics, 2012)
Toll-like receptors (TLRs), a large group of proteins which recognize various pathogen-associated molecular patterns, are critical for the normal function of the innate immune system. Following their discovery many single nucleotide polymorphisms within TLRs and components of their signaling machinery have been discovered and subsequently implicated in a wide range of human diseases including atherosclerosis, sepsis, asthma, and immunodeficiency. This review discusses the effect of genetic variation on TLR function and how they may precipitate disease.
Keywords: Toll-like receptors